Staff Guidance Note for Public Debt Sustainability Analysis in Market-Access Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
The framework for fiscal policy and public debt sustainability analysis (DSA) in market-access countries (MACs) was reviewed by the Executive Board in August 2011.1 The review responded to shortcomings in identifying fiscal vulnerabilities and assessing risks to debt sustainability against the backdrop of increased concerns over fiscal policy and public debt sustainability in many advanced economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet